Osteochondroma of the Scapula with Accessory Nerve (XI) Compression - Philippe Beauchamp-Chalifour; Stéphane Pelet (Case Reports in Orthopedics)
Osteochondroma is the most common benign bone tumor and is characterized as a cartilage-capped bony stalk. This lesion usually develops from the growth plate of long bones. Most osteochondromas are asymptomatic. Neurovascular compressions or cosmetic issues can occur in specific locations. Malignant transformation is extremely rare, and MRI can help evaluate these lesions. Symptomatic mass and malignancy features are the main surgical indications. Uncommonly, an osteochondroma can develop from flat bones. We present the case of a 25-year-old patient with a right scapula osteochondroma causing an accessory nerve compression. The mass was surgically removed, and the diagnosis was confirmed. The patient fully recovered at the latest 3-year follow-up visit.